Native experts and reputable journals as points of reference: A study on research-article discussions - Salmani Nodoushan, Mohammad Ali (Universitas Syiah Kuala, 2023)
The current study sought to compare the rhetorical moves and steps that native-English-speaking and Iranian authors of research articles (RAs) employ in writing up the discussion sections of their RAs. It was hypothesized that the latter group is not as proficient in writing RA discussions as the former group. A total of 66 (N=66) RA discussions from three reputable international academic journals and three Iranian journals were sampled from years 2009 to 2019. This corpus was then analyzed by three human coders who used Yang and Allisons (2003) rhetorical move analysis model for scoring the sampled RA discussions. Results showed stark differences between Iranian and native RA writers; the majority of the rhetorical moves and steps that are considered obligatory or conventional by the native group are seen as options by the Iranian group. With the native group and the reputable international journals being the standard points of reference, it was concluded that Iranian authors of RAs lack the professional knowledge and expertise prerequisite to writing standard RA discussions. It is recommended (a) that non-native authors of RAs receive professional training for writing standard discussions, and (b) that journal editors be more sensitive to rhetorical moves and steps before they accept a submission for publication.